Grid impedance estimation for islanding detection and adaptive control of converters - Ghanem, A.; Rashed, Mohamed; Sumner, M.; Elsayes, M.A.; Mansy, I.I.I. (IET, 2017)
Power system (grid) impedance is time varying due to the changing structure of the power system configuration and it can have a considerable influence on the control and stability of grid connected converters. This paper presents an online grid impedance estimation method using the output switching current ripple of a SVPWM based grid connected converter. The proposed impedance estimation method is derived from the discretised system model using two consecutive samples within a single switching period. The estimated impedance is used for islanding detection and online current controller parameter tuning. Theoretical analysis and MATLAB simulation results are presented to verify the proposed method and its effectiveness is validated using experimental testing.